The Impact of Public Spending Structure On Economic Growth ( Case Study of Syria ) - صندوق عفيف (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to study the effect of public spending policy in Syria on economic growth for the period between 2004-2018, by studying the integration of current and investment spending variables and their impact on economic growth using the Johansen Test for Joint Integration and the Vector Error Correction Model (VECM) for annual data. The study concluded that there is a first-degree integration of public spending variables in Syria. However, there is no effect of the current and investment spending variables on economic growth in the long or short term.